1982
DOI: 10.1136/gut.23.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Antral gastrin-producing G-cells and somatostatin-producing D-cells in different states of gastric acid secretion.

Abstract: SUMMARYThe number of G-and D-cells per area and the ratio of G/D-cells were investigated in biopsy specimens of the pyloric antrum from normochlorhydric subjects without peptic ulcer, from patients with duodenal ulcer, gastrinoma, pernicious anaemia, and after selective proximal vagotomy. Compared with normochlorhydric subjects antral G-cell density was significantly raised in pernicious anaemia, unchanged in duodenal ulcer, and diminished in gastrinoma patients. After vagotomy G-cell density was found to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
0
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(36 citation statements)
references
References 28 publications
5
30
0
1
Order By: Relevance
“…a pronounced increase in G cell volume density combined with a decrease in D cell volume density and consequently a marked increase in the G/D cell ratio. These observa tions gave support to the hypothesis that the antral G/D cell ratio is governed by the intragastric pH [ 18]. Again, changes of that order of magnitude have not been observed in this study in humans.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…a pronounced increase in G cell volume density combined with a decrease in D cell volume density and consequently a marked increase in the G/D cell ratio. These observa tions gave support to the hypothesis that the antral G/D cell ratio is governed by the intragastric pH [ 18]. Again, changes of that order of magnitude have not been observed in this study in humans.…”
Section: Discussionsupporting
confidence: 74%
“…Since the physiolog ical fasting serum gastrin levels in our radio immunoassay do not exceed 60 pg/ml, part of the gastrin concentration increase was caused by the 'preperiod' of unsuccessful ranitidine treatment [17], The hypergastrinaemia is believed to be due to a negative feedback mechanism between intragastric pH and antral gastrin cell activity [8,17,18]. The further increase in gastrin levels after initiation of omeprazole therapy is probably a consequence of the stronger and more per manent suppression of gastric acid secretion by the benzimidazole derivative in compari son to the H2 receptor antagonist [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic application of acidinhibitory drugs elevates serum gastrin levels (14,16,30), and it has been suggested that the gastric pH influences the population of endocrine cells such as gastrinproducing G cells (30)(31)(32). The long-term elevation of gastric pH may increase G-cell density and then elevate serum gastrin levels.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in G cell volume density is explained by feedback regulation and the decreased intragastric acidity results in a decrease in D cell volume density, since D cell growth is dependent on the stimulation of gastric acidity. 21,22) In this study, long-term administration of PAN·Na did show a tendency to increase G cell volume density, serum gastrin levels, parietal cell volume density, or mucosal thickness in the antrum, or a tendency to decrease D cell volume density. However, the increases in G cell and parietal cell volume densities in rats fed lower concentrations of (-)-PAN·Na and (±)-PAN·Na were more obvious than in rats fed higher concentrations of (-)-PAN·Na and (±)-PAN·Na.…”
Section: Discussionmentioning
confidence: 95%